2011
DOI: 10.1075/etc.4.2.05xu
|View full text |Cite
|
Sign up to set email alerts
|

English as a Lingua Franca in Flanders

Abstract: This article reports on a study that examines the attitudes of 69 Flemish university students towards the emerging conceptualization of English as a lingua franca (ELF) on the basis of a questionnaire survey. Built on the notion of ELF as a functional term theorized on sociolinguistic grounds, this study seeks to understand the relation between ELF as a theoretical construct and ELF as a reality in the life of these language students through their experiences of engagement with English, both within and outside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…In other words, they chose intelligibility over accuracy for successful communication. A similar conclusion was presented in the study conducted by Xu and Van de Poel (2011) which emphasized that English is recognized as a highly essential means of intelligibility in international communication by non-native speakers. Majority of the ESP students in the study indicated their adherence to the view that the attainment of communicative competence in English was more important than the attainment of linguistic accuracy, which goes in parallel with the claim of Widdowson (1983), in which he put forward the idea that mastering communicative competence, which includes components to clarify a speaker's utterances for achieving intelligibility, is preferred by, especially, non-native speakers to overcome misunderstandings and possible problems in the course of interaction with other speakers.…”
Section: Araştırma Makalesi / Research Papersupporting
confidence: 83%
“…In other words, they chose intelligibility over accuracy for successful communication. A similar conclusion was presented in the study conducted by Xu and Van de Poel (2011) which emphasized that English is recognized as a highly essential means of intelligibility in international communication by non-native speakers. Majority of the ESP students in the study indicated their adherence to the view that the attainment of communicative competence in English was more important than the attainment of linguistic accuracy, which goes in parallel with the claim of Widdowson (1983), in which he put forward the idea that mastering communicative competence, which includes components to clarify a speaker's utterances for achieving intelligibility, is preferred by, especially, non-native speakers to overcome misunderstandings and possible problems in the course of interaction with other speakers.…”
Section: Araştırma Makalesi / Research Papersupporting
confidence: 83%
“…Additionally, in a study that included 69 undergraduate English learners, Xu and Van de Poel [8] discovered that English is recognized as a highly essential means for international communication rather than for connecting socially with native speakers. Also, the study revealed that at a micro level, participants demonstrated a preference for linguistic accuracy measured against the native speaker standard form.…”
Section: Students' Attitudes and Perceptions Towards Eflmentioning
confidence: 99%
“…Xu & Van de Poel, 2011). Indeed, by using social media, learners get the opportunity to create personal content that can be shared with other users (cf.…”
Section: Recommendation Iv: Develop Didactic Approaches and Methodolomentioning
confidence: 99%